Drug delivery to bone using phosphonate as the bone-targeting substance - Tang, Kang Min. (2010)
This report presents a study on the use of phosphonates, as the bone-targeting substance in drug delivery systems. The purpose is to do a surface modification of calcium phosphate-based drug carriers with the bone targeting substance, forming a targeted drug delivery system. In this study, monophosphonates were used for the synthesis of this system. This was done by attaching the phosphonate end of amino phosphonates to hydroxyapatite, in replacement of calcium phosphate on the drug carrier. Carboxyl phosphonates are then attached to the amino phosphonates via the peptide bond, hence forming the targeted drug delivery system. Affinity to hydroxyapatite of the bone-targeting compound has been tested and proven through the use of FTIR spectroscopy as well as the Nanosizer. Characterization using FTIR showed that the amino phosphonate had successfully binded to hydroxyapatite. Results from the nanosizer also showed that a stable colloidal system was formed by hydroxyapatite and amino phosphonate. In addition, the formation of the peptide bond was also observed using FTIR with the peaks belonging to the peptide bond present. This design of a targeted drug delivery system can thus be used for active targeting of drugs from the carrier directly to bones. This study suggests that other classes of phosphonates, such as bisphosphonates that display increased affinity to bones can be also be used in a similar manner in the drug delivery system.